Classification of visual field abnormalities in highly myopic eyes without pathologic change - Lin, Fengbin; Chen, Shida; Song, Yunhe; Li, Fei; Wang, Wei; Zhao, Zhenni; Gao, Xinbo; Wang, Peiyuan; Jin, Ling; Liu, Yuhong; Chen, Meiling; Liang, Xiaohong; et al. (Ophthalmology, 2022)
Purpose - To develop a classification system of visual field (VF) abnormalities in highly myopic eyes with and without glaucoma. - Design - Secondary analysis of VF data from a longitudinal cohort study. - Participants - One thousand eight hundred ninety-three VF tests from 1302 eyes (825 individuals). - Methods - All participants underwent VF testing (Humphrey 24-2 Swedish interactive threshold algorithm standard program; Carl Zeiss Meditec) and detailed ophthalmic examination. A comprehensive set of VF defect patterns was defined via observation of the 1893 VF reports, literature review, and consensus meetings. The classification system comprised 4 major types of VF patterns, including normal type, glaucoma-like defects (paracentral defect, nasal step, partial arcuate defect, arcuate defect), high myopia-related defects (enlarged blind spot, vertical step, partial peripheral rim, nonspecific defect), and combined defects (nasal step with enlarged blind spot). A subset (n = 1000) of the VFs was used to evaluate the interobserver and intraobserver agreement and weighted κ values of the classification system by 2 trained readers. The prevalence of various VF patterns and their associated factors were determined. - Main Outcome Measures - The classification of VF in highly myopic eyes and its associated risk factors. - Results - We found that normal type, glaucoma-like defects, high myopia-related defects, and combined defects accounted for 74.1%, 10.8%, 15.0%, and 0.1% of all unique VF tests, respectively. The interobserver and intraobserver agreements were > 89%, and the corresponding κ values were 0.86 or more between readers. Both glaucoma-like and high myopia-related VF defects were associated with older age (odds ratios [ORs], 1.07 [95% confidence interval (CI), 1.04-1.10; P < 0.001] and 1.06 [95% CI, 1.04-1.10; P < 0.001]) and longer axial length (ORs, 1.65 [95% CI, 1.32-2.07; P < 0.001] and 1.37 [95% CI, 1.11-1.68; P = 0.003]). Longer axial length showed a stronger effect on the prevalence of glaucoma-like VF defects than on the prevalence of high myopia-related VF defects (P = 0.036). - Conclusions - We propose a new and reproducible classification system of VF abnormalities for nonpathologic high myopia. Applying a comprehensive classification system will facilitate communication and comparison of findings among studies.
Online verfügbar: 12 March 2022, Artikelversion: 20 June 2022
Gesehen am 05.12.2023